Innovative Technologies to Promote Sustainable Recirculating Aquaculture in Eastern Africa—A Case Study of a Nile Tilapia (Oreochromis niloticus) Hatchery in Kisumu, Kenya. (17th July 2020) - Clough, Samuel; Mamo, Julian; Hoevenaars, Kyra; Bardocz, Tamas; Petersen, Paw; Rosendorf, Poul; Atiye, Tahla; Gukelberger, Ephraim; Guya, Edwin; Hoinkis, Jan
ABSTRACT: Lake Victoria, regionally important both as a source of food and income, is under pressure due to overfishing and severe pollution. Currently, the vast majority of east African aquaculture is open‐pond based. The adoption of modern and sustainable aquaculture technologies and practices—in this case study recirculating aquaculture systems (RAS)—will help the region increase food security and decrease its current reliance on imported fish and stressed wild stock. To this end, VicInAqua, a project under the EU Horizon 2020 program, has developed a pilot Nile Tilapia ( Oreochromis niloticus ) hatchery in Kisumu, Kenya using RAS adapted to local conditions. The hatchery is designed as a flexible, scalable, and modular system. An online monitoring system enables farmers to access farm data from both fish tanks and the supporting renewable energy systems, allowing around‐the‐clock monitoring and control. The hatchery is linked to a 14.3 kWp Photovoltaic (PV) system, including a 30 kWh Li‐battery storage, to supply sustainable electricity. The water for the RAS, treated by a membrane bioreactor (MBR) and certified for use in aquaculture and agriculture, comes chiefly from Kisumu's municipal sewage, which reduces the farms' reliance on an expensive and occasionally intermittent potable water supply. Combining these technologies represents an industry first and offers a working example for larger‐scale future developments. The purpose of the project is to demonstrate the possible technologies and practices in situ as well as provide a template for future development and investment. The hatchery is used by the Department of Livestock, Agriculture and Fisheries, Kisumu County, Kenya, as a training and demonstration facility to promote the aquaculture sector and increase the awareness, knowledge, and skills of fish farmers, as well as provide high quality fingerlings to cage farmers within the lake. Integr Environ Assess Manag 2020;16:934–941. © 2020 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: VicInAqua, an EU horizon funded project, developed and implemented a sustainable and working recirculating aquaculture system (RAS) in Kisumu County, Kenya. Water for the RAS is primarily sourced from municipal sewage, treated using a membrane bioreactor and certified for use in aquaculture. Designed as a flexible, modular system, RAS offers an example for the future development of advanced aquaculture in the region. The RAS supplies local farmers with high quality, all‐male fingerlings, as well as providing a platform for training and technology dissemination.